2006
DOI: 10.1381/096089206776327288
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Childhood Sexual Abuse and Other Forms of Maltreatment to 12-Month Postoperative Outcomes in Extremely Obese Gastric Bypass Patients

Abstract: Extremely obese patients who seek gastric bypass surgery report higher rates of childhood maltreatment than normative community samples. A history of childhood maltreatment, including reports of sexual abuse, does not appear to be a negative prognostic indicator for gastric bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 23 publications
8
84
2
1
Order By: Relevance
“…With regard to weight loss, no difference was found between patients with and without history of abuse, at least for the first postoperative year. A further study by Grilo et al (2006) yielded similar findings. Of 137 patients, 32% reported sexual abuse and 27% emotional abuse in childhood.…”
Section: Posttraumatic Stress Disorderssupporting
confidence: 66%
“…With regard to weight loss, no difference was found between patients with and without history of abuse, at least for the first postoperative year. A further study by Grilo et al (2006) yielded similar findings. Of 137 patients, 32% reported sexual abuse and 27% emotional abuse in childhood.…”
Section: Posttraumatic Stress Disorderssupporting
confidence: 66%
“…Critical reviews of the empirical literature conclude that such concerns have yet to be empirically established (Gustafson & Sarwer, 2004), and recent prospective studies with established assessment methods have reported that high levels of sexual abuse (Grilo, White, Masheb, Rothschild, & Burke-Martindale, 2006;Larsen & Geenen, 2005) and other forms of childhood maltreatment (Grilo et al, 2006) do not appear to represent negative prognostic indicators for bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood sexual abuse and maltreatment, while more prevalent in the severely obese population (Grilo et al, 2005;Wildes, Kalarchian, Marcus, Levine, & Courcoulas, 2008), do not appear to have any relationship with postsurgical weight loss (Fujioka, Yan, Wang, & Li, 2008;Grilo, White, Masheb, Rothschild, & Burke-Martindale, 2006). Presurgical life stress, in and of itself, does not appear to have a negative impact on weight loss (Herpertz et al, 2004;van Hout et al, 2005).…”
Section: What Is Known -Paradoxical Resultsmentioning
confidence: 98%